Digital Marketing for Public Sector Services – The Traffic Safety Experience in the United Arab Emirates- - Karima Boussag (المجلة الدولية للأداء الاقتصادي)
This research paper aims to highlight the importance of using digital marketing in public sector organizations, with particular attention to public security institutions in providing their services and effectively communicate safety awareness messages and persuading the public of their importance. A descriptive approach was adopted to achieve the desired objectives, supported by the experience of one of the Arab countries in this field. The study concludes that strengthening digital marketing activities can assist countries, especially public security organizations, in reducing traffic accidents and raising awareness amongst public.